The Implementation of Adat Land Law (Study of Adat Land of Grand Sultan Tanjungbalai) - Rahmat, Rahmat; Nasution, Emmi Rahmiwita; Bima, Meirad Arianza (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2024)
This study aims to examine the tactics used by the Tanjungbalai City Land Office to register Sultan Grant land. The study employs a qualitative technique with a descriptive approach, concentrating on the context and persons engaged in the Sultan Grant land registration process at the Tanjungbalai City Land Office. The data highlight various barriers to registering Sultan Grant land. The strategies for registering Sultan Grant land include: first, registering the Sultan Grant and then following the procedure for confirming conversion or recognizing rights; second, for Sultan Grants that have been transferred to another party, registering the land through the former Sultan's state land Grant procedure; and third, for Sultan Grants that are not yet registered, treating the registration as an application